NDAT suppresses pro-inflammatory gene expression to enhance resveratrol-induced anti-proliferation in oral cancer cells. (February 2020) - Ho, Yih; Wu, Chien-Yi; Chin, Yu-Tang; Li, Zi-Lin; Pan, Yi-shin; Huang, Tung-Yung; Su, Po-Yu; Lee, Sheng-Yang; Crawford, Dana R.; Su, Kuan-Wei; Chiu, Hsien-Chung; Shih, Ya-Jung; et al.
Abstract: Nano-diamino-tetrac (NDAT), a tetraiodothyroxine deaminated nano-particulated analog, has shown to inhibit expression of pro-inflammatory genes. NDAT inhibits expression of programmed death-ligand 1 ( PD-L1 ). On the other hand, in addition to inhibiting inflammatory effect, the stilbene, resveratrol induces expression of cyclooxygenase-2 ( COX-2 ) and its accumulation. Sequentially, inducible COX-2 complexes with p53 and induces p53-dependent anti-proliferation. In current study, we investigated mechanisms involved in combined treatment of NDAT and resveratrol on anti-proliferation in human oral cancer cells. Both resveratrol and NDAT inhibited expression of pro-inflammatory IL-1β and TNF-α . They also inhibited expression of CCND1 and PD-L1 . Both resveratrol and NDAT induced BAD expression but only resveratrol induced COX-2 expression in both OEC-M1 and SCC-25 cells. Combined treatment attenuated gene expression significantly compared with resveratrol treatment in both cancer cell lines. Resveratrol reduced nuclear PD-L1 accumulation which was enhanced by a STAT3 inhibitor, S31-201 or NDAT suggesting that NDAT may inactivate STAT3 to inhibit PD-L1 accumulation. In the presence of T4, NDAT further enhanced resveratrol-induced anti-proliferation in both cancer cell lines. These findings provide a novel understanding of the inhibition of NDAT in thyroxine-induced pro-inflammatory effect on resveratrol-induced anticancer properties.